2021
DOI: 10.1097/md.0000000000026547
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors with constipation and health-related quality of life in lung cancer patients with platinum-based chemotherapy

Abstract: The main purpose of this study was to investigate current state of constipation for lung cancer (LC) patients receiving platinum-based chemotherapy. The relationships between social demography, clinical variables, psychological status, and constipation were analyzed. In addition, quality of life (QoL) in LC patients with constipation was also analyzed. One hundred LC patients participated in this cross-sectional study. Under the guidance of the researchers, Functional Living Index-Emesis, Piper Fatigue Scale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…However, it is seen that the effect of constipation on quality of life after chemotherapy in adult patients has been investigated more [18,19,20]. Rha and Lee's study found that constipation had a negative impact on quality of life [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is seen that the effect of constipation on quality of life after chemotherapy in adult patients has been investigated more [18,19,20]. Rha and Lee's study found that constipation had a negative impact on quality of life [20].…”
Section: Discussionmentioning
confidence: 99%
“…The internal consistency of each item was 0.89-0.94, and the reliability of the total score was 0.92 (Xiao, 1994). This scale has been used in patients with lung cancer and shows high reliability (Chen, Gu, et al, 2021).…”
Section: Social Support Rating Scale (Ssrs)mentioning
confidence: 99%
“…In addition, a study reported that, during the COVID-19 pandemic, one-fourth of the population developed new-onset functional constipation symptoms and lower water consumption due to related lockdown measures and the resulting reduction in physical activity [ 10 ]. Moreover, constipation has been reported to have a significant impact on quality of life [ 11 ] and associated with depression [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent literature review on fatigue in community-dwelling older adults reported various factors related to fatigue, including biological (inflammation, energy, pain, adiposity, low hemoglobin, and tooth loss), psychological (depressive symptoms and stress), behavioral (sleep, physical activity, and malnutrition), and social factors (social support) [ 13 ]. A study of patients with lung cancer receiving platinum-based chemotherapy found that reduced food intake and fatigue were the main factors affecting functional constipation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation